Self-monitoring in third year medical students’ haematology clerkships - Vuma, Sehlule; Sa, Bidyadhar (International Journal of Research in Medical Sciences, 2017)
Background: Self-monitoring by medical students is important for continued learning and development. It results in self-awareness and improved performance. It requires self-motivation, attentiveness and curiosity. However, students don’t have skills for self-monitoring when they enter university. These need development. The objective of the study was to evaluate the use of an online formative assessment, on subsequent summative examination performance in haematology clerkships among third-year medical students. Methods: Results of a formative, multiple choice question (MCQ) quiz were correlated with results of end of clerkship (EOC) summative examinations (free-response short-answer progressive disclosure questions-PDQ, and spotter-MCQ). t-ratio was calculated between students who took the quiz (responders) and non-responders. Descriptive statistics, Pearson correlations (r), and Chi square (χ2) were performed. Results: Of 241 students 75 (31.1%) took the quiz. t-ratio was 1.864 (P>0.05). Mean scores for EOC were higher for responders. Failure rate was higher for non-responders. Between the EOC-PDQ and EOC-spotter, for the whole group (N=241), r=0.414, for non-responders, (N=166), r=0.376, and responders r=0.473. For the responders, correlations between the quiz and PDQ, r=0.376, and between quiz and spotter, r=0.222. χ2 was significant at P<0.05. Conclusions: Quiz exercises are useful self-monitoring strategies. However online exercises require self-motivation. Students may not wish to do exercises that don’t count for summative scores. They should be encouraged to engage in these learning exercises. Timing is important. For the majority of students, the quiz was done the same week as PDQ for another course. Students chose to prioritize and concentrate on the summative PDQ. These exercises in themselves, would be useful time management lessons.